Correction: Metal-free oxidative synthesis of benzimidazole compounds by dehydrogenative coupling of diamines and alcohols. Issue 16 (11th April 2022) - Hu, Jiaming; Li, Mengjia; Wan, Jing; Sun, Jinnan; Gao, Hu; Zhang, Feng; Zhang, Zhibing
Abstract : Correction for 'Metal-free oxidative synthesis of benzimidazole compounds by dehydrogenative coupling of diamines and alcohols' by Jiaming Hu et al., Org. Biomol. Chem., 2022, DOI: ; 10.1039/d2ob00165a .